Effect of auxin inhibitor and AMF inoculation on growth and root morphology of trifoliate orange (Poncirus trifoliata) seedlings - LIU, CHUN-YAN; SRIVASTAVA, A K; WU, QIANG-SHENG (The Indian Journal of Agricultural Sciences, 2014)
Auxins are considered as one of the important plant hormones coordinating the signals in regulation of plant development including the transformation in root morphology. Arbuscular mycorrhizal fungi (AMF) produce small amount of auxins, the role of which is yet not known in root and mycorrhizal development. The present study was undertaken to evaluate the effects of AMF (Glomus versiforme Karst.) and an auxin inhibitor (P- Chlorophenoxyisobutyric acid, PCIB, 10 mM) on plant growth and root development of four-month-old mycorrhized trifoliate orange [Poncirus trifoliata (L.) Raf.] seedlings. Root mycorrhizal colonization and number of entry points and vesicles were significantly inhibited by exogenous PCIB treatment, suggesting that auxins are involved in establishment of AMF-host plant symbiosis. Application of PCIB significantly decreased the plant height, stem diameter, leaf number, and shoot and root fresh weight. On the other hand, AMF colonization increased the plant height, shoot and root fresh weight, thereby, suggesting that AMF colonization alleviated the negative effects of PCIB. Similarly, PCIB application significantly decreased taproot length, root average diameter, roots projected area, surface area of roots, root volume, root length under 0–1 cm category, and total root length. These root traits significantly improved upon inoculation with AMF. The study, hence, suggested that inoculation with AMF negated the adverse effects of PCIB through AMF-induced auxin production that actively participated in both root and mycorrhizal plant development.